Kajian Ekonomis Penambangan Batubara Dengan Menggunakan Metode Benefit Cost Rasio Pada Blok N21 IUP PT. Alfara Delta Persada Kecamatan Anggana Kabupaten Kutai Kartanegara, Kalimantan Timur - Zulni Eldo Putra; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. Alfara Delta Persada is a coal mining company which is currently planning to minethe N21 block. Previously, this block had been mined but stopped due to the influx of the Kutairiver to the excavated N21 pit, as a result the former excavation became a lake. In line with thefall in coal prices at that time in 2013 mining in the N21 block was totally stopped. In thisresearch the method used is descriptive quantitative method. Where this research will producecost and benefit calculations based on data from excavated volumes and stockpiles, which arethen analyzed using the Benefit Cost Ratio method to determine their economic viability.Basedon the results of the study it can be seen that the costs or costs that must be incurred to conductmining in the N21 block are Rp.52,557,921,531.79, and generate benefits of Rp.170,118,527,384.02 from the results of the analysis using the Benefit Cost Ratio methodresulting in a BCR value of 3.24, meaning that the value is BCR> 1 which results in a feasible oreconomic decision criteria for mining.Keywords : Benefit Cost Ratio, Economic Studies, Coal, Productivity, Cash Flow